2009
DOI: 10.1063/1.3079401
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of organic single-crystal transistors gated with various ionic-liquid electrolytes

Abstract: We report on a comparative study of rubrene single-crystal field-effect transistors with various ionic-liquid electrolytes used for gate insulators. A systematic correlation is found that mobility of the field-effect transistors increases with decreasing electrostatic capacitance of the electric double layers, as the result of highly reproducible comparisons among tens of samples with the variation of anions in the purified ionic liquids. By optimizing the gating ionic liquid, the highest mobility of the elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
153
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 160 publications
(168 citation statements)
references
References 24 publications
14
153
1
Order By: Relevance
“…To this end, we have fabricated N , NЉ-bis͑n-alkyl͒-͑1,7 and 1,6͒-dicyanoperylene-3,4:9,10-bis͑dicarboximide͒s ͑PDIF-CN 2 ͒ single-crystal transistors with IL, using the same methods used for p-type rubrene single crystals. 16,17 As organic material we have selected PDIF-CN 2 , 19,20 which exhibits the highest electron mobility reported to date ͑1-6 cm 2 / V s͒. 21 We show that the electron mobility of PDIF-CN 2 single-crystal transistors with IL ͑as high as 5.0 cm 2 / V s in air͒ is comparable to the corresponding devices without IL, thus having air as gate dielectric.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…To this end, we have fabricated N , NЉ-bis͑n-alkyl͒-͑1,7 and 1,6͒-dicyanoperylene-3,4:9,10-bis͑dicarboximide͒s ͑PDIF-CN 2 ͒ single-crystal transistors with IL, using the same methods used for p-type rubrene single crystals. 16,17 As organic material we have selected PDIF-CN 2 , 19,20 which exhibits the highest electron mobility reported to date ͑1-6 cm 2 / V s͒. 21 We show that the electron mobility of PDIF-CN 2 single-crystal transistors with IL ͑as high as 5.0 cm 2 / V s in air͒ is comparable to the corresponding devices without IL, thus having air as gate dielectric.…”
mentioning
confidence: 99%
“…For p-type transistors ͑based on rubrene͒ it was also recently found that the surface of organic semiconductors is not damaged by the ILs, and mobility values up to 9.5 cm 2 / V s can be achieved by selecting the proper IL. 17 For n-type OFETs with EDL gating, however, virtually nothing is known at this stage.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…18,19) This configuration has attracted interest for an organic polymer FET with a polymer electrolyte solution with high on-state conductance 20,21) and an organic single crystal FET with low on-state gate bias. [22][23][24][25] An oxide FET device with an electrolyte solution was first reported on ZnO and a polymer electrolyte, and high-density carrier accumulation was also reported for a device with an ionic liquid as an electrolyte. 26,27) The device configuration is schematically illustrated in Fig.…”
Section: Device Configurationmentioning
confidence: 99%